2021
DOI: 10.1212/nxi.0000000000000906
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase 3–like 1 and neurofilament light chain in CSF and CNS atrophy in MS

Abstract: ObjectiveTo investigate cross-sectional associations of CSF levels of neurofilament light chain (NfL) and of the newly emerging marker chitinase 3–like protein 1 (CHI3L1) with brain and spinal cord atrophy, which are established MRI markers of disease activity in MS, to study CHI3L1 and NfL in relapsing (RMS) and progressive MS (PMS), and to assess the expression of CHI3L1 in different cell types.MethodsIn a single-center study, 131 patients with MS (42 RMS and 89 PMS) were assessed for NfL and CHI3L1 concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 37 publications
(59 reference statements)
3
26
0
Order By: Relevance
“…Interestingly, we observed that the presence of monocytes/macrophages was associated with conversion to CDMS. This underlines findings on Chitinase 3like 1 (CHI3L1), a glycoprotein secreted by macrophages (41), which was determined as a biomarker in MS (42)(43)(44) and which was also associated with the conversion from CIS to CDMS (45).…”
Section: Discussionsupporting
confidence: 76%
“…Interestingly, we observed that the presence of monocytes/macrophages was associated with conversion to CDMS. This underlines findings on Chitinase 3like 1 (CHI3L1), a glycoprotein secreted by macrophages (41), which was determined as a biomarker in MS (42)(43)(44) and which was also associated with the conversion from CIS to CDMS (45).…”
Section: Discussionsupporting
confidence: 76%
“…Similarly, being in remission or in relapse does not influence the CSF levels of RRMS patients [ 144 ]. In contrast, higher levels were associated with increased numbers of T2 and Gd+ enhancing lesions on MRI scans and faster disability progression, fulminant disease course [ 149 ] and hastened spinal cord atrophy [ 150 , 151 , 152 , 153 , 154 , 155 , 156 ]. Furthermore, CHI3L1 proved to be a reliable marker for distinguishing between RR and progressive phenotype and forecasting disability progression when measured together with the neurofilament light chain (NFL) [ 157 ].…”
Section: Fluid Biomarkers Of Multiple Sclerosismentioning
confidence: 99%
“…Natalizumab, fingolimod and mitoxantrone were found to reduce CSF levels of CHI3LI1 in RRMS patients, while for interferon-beta, the same was true only for treatment responders [ 153 , 158 , 159 ]. On the other hand, glatiramer acetate [ 156 ] and dimethyl fumarate (at least in patients with progressive disease [ 158 ]) did not influence CHI3L1 levels.…”
Section: Fluid Biomarkers Of Multiple Sclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study examining the value of cNfL and CHI3L1 concluded that CHI3L1 levels were associated with spinal cord volume loss but not with brain gray matter atrophy. In contrast, cNfL was associated with brain but not with spinal cord volumes ( Schneider et al, 2021 ). The combined measurement of CHI3L1 + cNfL could therefore provide complementary information on the location of atrophy in pwMS.…”
Section: The Known Unknownsmentioning
confidence: 99%